Assessment in Differentiated Learning in Mathematics Lessons (Journal of Educational Sciences, 2023)
Updating the content of mathematics curricula is aimed at developing the functional literacy of students. Mathematics, being one of the most difficult subjects to study in a school course, requires the teacher to consider the individual characteristics of students, and groups of students when planning a lesson, identified by the results of the assessment. Assessment is an integral part of the educational process, which provides information to the teacher about the results of students' learning in the acquiring of educational material, and the development of students' mathematical skills. This information allows the teacher to respond promptly and select such teaching and learning methods that will be more effective at this stage of learning. Effective lesson planning allows students to organize their activities so that they are constantly in their "zone of proximal development", which contributes to the development of their mathematical abilities.The authors explore the issue of using assessment to organize a differentiated approach to teaching mathematics. During the study, a review of domestic and foreign literature on the issues of assessment and the use of a differentiated approach in the educational process was carried out. The points of view of various authors on these issues are considered both in the conditions of traditional and distance (blended) education. A survey was organized and conducted to identify students' opinions about how they are taught and evaluated in mathematics lessons. This article describes the results of a survey of students studying in rural and urban schools, based on their opinion, an analysis is made of the current needs of teachers in the field of assessment. The conducted literature review, as well as the results of the survey, formed the basis for the conclusions and recommendations for teachers in the field of assessment.Keywords: assessment, differentiated approach, learning process, mathematics.